Breaking Barriers: Unraveling the Complexities of HR Tech Integration - Muktamar, Ahmad; Nurnaningsih A, Nurnaningsih A (Penelitian dan Pengembangan Ilmu, 2024)
This research aims to explore the factors that influence technology adoption by the Human Resources (HR) Department. The research method used is a systematic literature review using academic databases of international reputation over the last ten years. Research findings indicate that factors such as organizational culture, technology adoption, HR competencies, HR analytics, technology availability and accessibility, symbolic adoption, and organizational factors play an important role in HR technology adoption. An organizational culture that supports innovation and technology, as well as the technological competence possessed by HR personnel, are significant factors in influencing technology adoption. Additionally, adequate technology availability and strong organizational support were also found to contribute to higher technology adoption rates. The implications of this research indicate the need for organizations to pay attention to these factors in an effort to increase HR technology adoption. Suggestions for future research include longitudinal research to evaluate the long-term impact of HR technology adoption, as well as research across industries and cultural contexts to understand the factors that influence HR technology adoption more broadly.